Pemahaman Konsep Mediasi Di Luar Pengadilan untuk Sengketa Perkawinan di Kota Banda Aceh, Aceh, Indonesia - Fanny Tasyfia Mahdy (Ar-Raniry: International Journal of Islamic Studies, 2020)
This study concerns about how the mediation process takes place within the families of the disputing parties and what may lead to mediation within the conflicting families. This qualitative study used the empirical legal research approach taking into account the research ethics at the UIN Ar-Raniry and the Covid-19 health protocol, and also employed library research as the supporting method. The primary data of this study came from interviews with the community leaders, local people, and village officials regarding the understanding and concept of mediation outside the court. The secondary data came from Aceh Qanun Number 9 of 2008 concerning Customary Life Development and Aceh Qanun Number 10 of 2008 concerning Customary Institutions. To analyze the data, the author used the following step: the data and information collected in the study, from interviews with related agencies, community leaders and local people, were examined using qualitative descriptive analysis, a data analysis method by grouping and selecting data obtained from research according to quality and correctness. The results showed that the community in general has been familiar with mediation as well as mutual deliberation and consensus in resolving domestic disputes occuring within their community. However, the people have had no understanding on the concept of mediation as regulated by the Qur’an, including the mediation stages described in the Qur’an.